Multi-electrode layout design of electrorheological composite plates considering energy consumption in semi-active control. (August 2021) - Liang, Kuan; Luo, Yangjun; Liu, Zhijun; Zhang, Xiaopeng; Kang, Zhan
Abstract: In the semi-active vibration control of structural systems, best control performance and low energy consumption both play important roles. This paper presents a new topology optimization method for the multi-electrode layout design of sandwich electrorheological (ER) plates considering limited energy consumption under different vibration conditions. In the proposed topology optimization model, the dynamic compliance under specified harmonic excitation is taken as the objective function, and a constraint of the maximum allowable energy consumption is considered. The frequency response analysis is implemented with finite element discretization, and the sensitivity analysis scheme of the control energy consumption for the design variables is derived with the adjoint-variable method. Numerical examples showed that optimal layouts of multi-electrodes could be obtained with different energy consumption requirements and loading conditions by using the proposed method. The excellent performance of vibration control could be achieved by only varying the voltage distribution of ERs. Highlights: A new topology optimization method for multi-electrode layout design of ER plates is proposed. Energy consumption constraint is considered in the vibration optimization model. Best vibration control performance can achieved by only switching the optimal electrode layouts. Frequency response sensitivity analysis for ER plate is derived with adjoint variable method.